2020
DOI: 10.3390/genes11040421
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Instability in Fungal Plant Pathogens

Abstract: Fungi and fungal-like organisms (oomycetes) that cause diseases in plants have impacted human communities for centuries and probably from the dawn of agriculture. In modern agriculture, there is a constant race between new strategies to manage fungal plant pathogens and their ability to adapt. An important component in this race is fungal genetic diversity. Mechanisms such as sexual and parasexual recombination that contribute to the creation of novel allele combinations in fungal plant pathogens are briefly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 115 publications
0
23
0
Order By: Relevance
“…The same biochemical or genetic plasticity which enables fungi to adapt to stressors ranging from climate changes and nutrient availability to internalized toxins from competing microbiota can also allow for adaptation to antifungals (Verweij et al, 2016a;Hokken et al 2019;Buil et al 2019;Covo 2020). Loss of genetic stability in fungal species such as Candida albicans and A. fumigatus has been associated with lessened susceptibility to triazole antifungals (Selmecki et al, 2009;Buscaino, 2019).…”
Section: Target Gene Mutation-independent Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The same biochemical or genetic plasticity which enables fungi to adapt to stressors ranging from climate changes and nutrient availability to internalized toxins from competing microbiota can also allow for adaptation to antifungals (Verweij et al, 2016a;Hokken et al 2019;Buil et al 2019;Covo 2020). Loss of genetic stability in fungal species such as Candida albicans and A. fumigatus has been associated with lessened susceptibility to triazole antifungals (Selmecki et al, 2009;Buscaino, 2019).…”
Section: Target Gene Mutation-independent Resistancementioning
confidence: 99%
“…2019; Buil et al . 2019; Covo 2020). Loss of genetic stability in fungal species such as Candida albicans and A. fumigatus has been associated with lessened susceptibility to triazole antifungals (Selmecki et al ., 2009; Buscaino, 2019).…”
Section: The Rise Of Resistancementioning
confidence: 99%
“…Understanding the evolution and population dynamics of fungal plant pathogens is key to enable an appropriate management of ecosystems in modern agriculture and to contain fungal infections, that otherwise would cause severe economic losses. Uncountable studies and outstanding review compilations have been already published on several groups of fungal pathogens as well as specifically on model species—such as those belonging to the genera Aspergillus , Fusarium and Verticillium , to mention just a few—to investigate evolving transposable elements and virulence genes that cause genomic plasticity and variation in virulence phenotypes [ 11 , 57 , 58 ]. Pedro et al [ 59 ] integrated genomic and phenotypic data from plant pathogen species into an expertly curated catalog of genes (PhytoPath) with experimentally verified pathogenicity, with the Ensembl tools for data visualization and analysis ( ).…”
Section: Genomic Advances In Ascomycotamentioning
confidence: 99%
“…These DNA regions are either islands of repetitive DNA or entire accessory, dispensable chromosomes [ 61 ], the sequences of which are structurally variable, so that the difficulty of assembling and comparing them makes the study of their evolutionary patterns particularly challenging [ 63 ]. Lineage-specific regions have been described in plant pathogens from different subphyla such as for Taphrina (Taphrinomycotina), Verticillium and Fusarium ([ 58 ] and references therein). It was supposed that genomic regions with a high density of repetitive elements are hot spots for the creation of new pathogenicity-associated, lineage-specific effector genes ([ 58 ], and references therein).…”
Section: Genomic Advances In Ascomycotamentioning
confidence: 99%
“…The genome of P. brassicae was assembled using Illumina Hiseq 2500 technology [ 164 ], while the A. candida genome was assembled using Roche/454 [ 165 ]; both are short-read sequencing technologies. These high-quality genome assemblies of the Brassica pathogens revealed that the fungal pathogens contain high genomic variation, including mutations largely induced by transposable elements (TE), large-scale chromosomal re-arrangements [ 166 , 167 ], presence–absence variation [ 168 ] and the gain or loss of accessory chromosomes [ 169 , 170 , 171 ]. These genetic events are continuously and actively evolving in the adaptive response to the selection pressure by the host plant resistance mechanism, thus generating high-genome-plasticity regions, which are often found distributed in compartments where most of the virulence genes are housed [ 172 ].…”
Section: Application Of Omics Technologies In Brassica mentioning
confidence: 99%